Neonatal oesophageal and axilla temperatures in the neonatal intensive care unit care. (15th October 2015) - Hoffman, Laurie; Santos, Mary Ann; Tucker, Richard; Laptook, Abbot
Abstract: Aim: To compare oesophageal and axilla temperatures in routine neonatal intensive care unit (NICU) care. Methods: Prospective observational study of NICU infants with indwelling oral/nasogastric tubes. Three simultaneous temperature measurements were taken: Physitemp axilla, digital Premie Faichney axilla in predictive mode and Physitemp oesophageal. Temperatures were measured on two separate days. Results: Fifty infants were studied over a range of gestational ages (median 28.9 weeks, IQR 25.8–30.6 weeks) and birthweights (median 1140 g, IQR 742–1498 g). Mean Physitemp oesophageal temperatures were 0.3 ± 0.1°C (range 0.1–0.6°C) higher than Physitemp axilla temperatures. After adjustment for weight, the Physitemp oesophageal–Physitemp axilla difference remained constant over the average oesophageal–axilla temperature range studied (p = 0.07). Physitemp oesophageal temperatures were not affected by weight (p = 0.2) or postmenstrual age (p = 0.51). Physitemp axilla temperatures decreased with increasing weight (p = 0.03) and postmenstrual age (p = 0.048). The Physitemp oesophageal–Physitemp axilla difference was greater for infants in cribs (mean ± SD = 0.4 ± 0.1°C) than in incubators (mean ± SD = 0.3 ± 0.1°C, p < 0.001). The relationship between oesophageal and digital Premie Faichney axilla temperature was similar to oesophageal and axilla Physitemp temperatures. Conclusion: Over a range of infant temperatures encountered in routine NICU care, oesophageal temperature is higher than axilla temperature, although the difference is small. Axillary temperatures measured by digital thermometers in predictive mode are comparable to core oesophageal temperatures.